Faktor-faktor Pemakai yang Mempengaruhi Minat Pemanfaatan Sistem Informasi - Hamzah, Ardi (Jurnal Akuntansi Multiparadigma, 2010)
The purpose of this research is to examine the effect performance expectancy, effort expectancy, social factors, fit to task and conditions that facilitate users on usage of information system at 4 regions government in Madura Island. The respondents of the research are employees who are using information technology system in their working environments. Data has been gathered by questionnaires and documentation. Sample total is 32 respondents. The result of research with partial regression indicates that performance expectancy, effort expectancy, and conditions which facilitate users of information system significantly affect usage of information system, while social factors and fit to task do not significantly affect usage of information system. The result of research with simultaneous regression indicates that performance expectancy, effort expectancy, social factors, fit to task and condition which facilitate users in using information system significantly affect usage of information system.